Role of β3‐adrenergic receptor in the modulation of synaptic transmission and plasticity in mouse cerebellar cortex. Issue 11 (17th August 2020) - Lippiello, Pellegrino; Hoxha, Eriola; Cristiano, Claudia; Malvicini, Emilia; Stanley, Adrien; Russo, Roberto; Tempia, Filippo; Miniaci, Maria Concetta
Abstract: Convergent lines of evidence have recently highlighted β3‐adrenoreceptors (ARs) as a potentially critical target in the regulation of nervous and behavioral functions, including memory consolidation, anxiety, and depression. Nevertheless, the role of β3‐ARs in the cerebellum has been never investigated. To address this issue, we first examined the effects of pharmacological manipulation of β3‐ARs on motor learning in mice. We found that blockade of β3‐ARs by SR 59230A impaired the acquisition of the rotarod task with no effect on general locomotion. Since the parallel fiber–Purkinje cell (PF–PC) synapse is considered to be the main cerebellar locus of motor learning, we assessed β3‐AR modulatory action on this synapse as well as its expression in cerebellar slices. We demonstrate, for the first time, a strong expression of β3‐ARs on Purkinje cell soma and dendrites. In addition, whole‐cell patch‐clamp recordings revealed that bath application of β3‐AR agonist CL316, 243 depressed the PF–PC excitatory postsynaptic currents via a postsynaptic mechanism mediated by the PI3K signaling pathway. Application of CL316, 243 also interfered with the expression of PF long‐term potentiation, whereas SR 59230A prevented the induction of LTD at PF–PC synapse. These results underline the critical role of β3‐AR on cerebellar synaptic transmission and plasticity and provide a new mechanism for adrenergic modulation of motor learning. Abstract : The present study is the first to investigate the localization and function of β3‐adrenoreceptor (AR) in the mouse cerebellum. The immunohistochemical analysis allowed us to demonstrate that β3‐AR is mainly expressed on Purkinje cells. In addition, we found that blocking β3‐AR interfered with motor learning and synaptic plasticity at the parallel fiber–Purkinje cell. The molecular mechanisms underlying the β3‐AR action are likely related to the activation of the PI3K signaling pathway in Purkinje cells.